Family Nutrition Education - Seń, Mariola (EDUsfera. Ewa Jurczyk-Romanowska, 2019)
The family environment is an extremely important place for its members, especially for the child, where their knowledge and skills are formed and their understanding of the influence of various factors and laws governing the processes affecting their health is developed. Parents/guardians are usually the first people to introduce the child to the world of heterogeneous concepts and experiences, helping him/her to understand the surrounding reality. It is from them that the child is taught to understand the concept of health, how to take care of health and food-related behaviour, indicating which foods are good for him/her and which will be undesirable. Parents are the first educators and providers of models and norms as well as desirable behavior and at the same time they supervise their observance. The aim of this article is to draw attention to the importance of nutrition education and the role of the family in the development of the child’s health. The child should learn appropriate health habits related to diet and adherence to the principles of proper nutrition from early childhood in connection with the influence of various factors and influences.
Keywords: family; eating behavior; food; education